Fostering Indonesian SMEs Performance: The Role of Supply Chain Networks and Supply Chain Flexibility - Riantani, Suskim; Kartadjumena, Eriana; Jayaatmaja, Muhamad Alan; Jaafar Sidik, Morni Hayati (ExcelingTech, 2019)
this examination is expected to investigate the effect of SC networks and SC flexibility in improving the Indonesian SMEs performance. SC integration has filled in as a mediator among the relationship between SC networks and SC flexibility with SMEs performance. This is a quantitative report. 146 workers were taken as an example estimate from SME's segments. Arbitrary examining procedure was utilized to gather the information. 5 point Likert scale was utilized to get the reaction. PLS-SEM The discoveries of this examination uncovered the positive noteworthy connections exist between SC networks, SC flexibility alongside the directing job of SC integration on Indonesian SMEs performance, which further affirms the proposed research reasonable structure for SMEs business performance.